Comparative analysis of processing methods in Robusta coffee in Uganda - Nakendo, S; Musoli, P C; Kananura, E; Wagoire, W W (Journal of Postharvest Technology, 2018)
Quality is a big factor in the retail structure at the international coffee stage. And, optimum postharvest handling, cherry processing inclusive, is vital in  ensuring the desired bean physical quality out. Here, Robusta cherries derived from different processing methods (naturals, pulped naturals and fully  washed coffees) were appraised for bean physical quality. The result in this trial indicates that complete wet processing method (fully washed  Robustas) had the highest moisture content retention, least bean borer infestation besides, least labour intensive at drying to 12% moisture and with  the least projections in US$ losses per 60kg bag of green bean.
Keywords: Coffee; Robusta; Processing; Uganda